PM2.5-related health and economic loss assessment for 338 Chinese cities - Maji, Kamal Jyoti; Ye, Wei-Feng; Arora, Mohit; Shiva Nagendra, S.M. (Environment international, 2018)
China is in a critical stage of ambient air quality management after global attention on pollution in its cities. Industrial development and urbanization have led to alarming levels of air pollution with serious health hazards in densely populated cities. The quantification of cause-specific PM2.5-related health impacts and corresponding economic loss estimation is crucial for control policies on ambient PM2.5 levels. Based on ground-level direct measurements of PM2.5 concentrations in 338 Chinese cities for the year 2016, this study estimates cause-specific mortality using integrated exposure-response (IER) model, non-linear power law (NLP) model and log-linear (LL) model followed by morbidity assessment using log-linear model. The willingness to pay (WTP) and cost of illness (COI) methods have been used for PM2.5-attributed economic loss assessment. In 2016 in China, the annual PM2.5 concentration ranged between 10 and 157 μg/m3 and 78.79% of the total population was exposed to >35 μg/m3 PM2.5 concentration. Subsequently, the national PM2.5-attributable mortality was 0.964 (95% CI: 0.447, 1.355) million (LL: 1.258 million and NPL: 0.770 million), about 9.98% of total reported deaths in China. Additionally, the total respiratory disease and cardiovascular disease-specific hospital admission morbidity were 0.605 million and 0.364 million. Estimated chronic bronchitis, asthma and emergency hospital admission morbidity were 0.986, 1.0 and 0.117 million respectively. Simultaneously, the PM2.5 exposure caused the economic loss of 101.39 billion US$, which is 0.91% of the national GDP in 2016. This study, for the first time, highlights the discrepancies associated with the three commonly used methodologies applied for cause-specific mortality assessment. Mortality and morbidity results of this study would provide a measurable assessment of 338 cities to the provincial and national policymakers of China for intensifying their efforts on air quality improvement. The spatial distributions of annual mean PM2.5 concentrations (μg/m3) (left) and corresponding total premature mortality per 100,000 population attributable to PM2.5 (right) in 338 cities in China. [Display omitted] •This study provides a comprehensive analysis of PM2.5 associated health risk in China using three most prevalent methods.•Total PM2.5-related death was 0.964 million using IER method, 1.258 million using LL and 0.770 million using NPL method.•Cities with high premature mortality were largely located in heavily polluted and densely populated regions.•Total economic loss due to PM2.5 exposure was 101.39 billion US$, about 0.91% of the total Chinese GDP.•Only 8.3% of total premature deaths could be avoided by meeting national PM2.5-target in 2030.